Engineering ethics : an industrial perspective - Baura, Gail D. (Elsevier Academic Press, 2006)
Engineering Ethics is the application of philosophical and moral systems to the proper judgment and behavior by engineers in conducting their work, including the products and systems they design and the consulting services they provide. In light of the work environment that inspired the new Sarbanes/Oxley federal legislation on "whistle-blowing#x94; protections, a clear understanding of Engineering Ethics is needed like never before. Beginning with a concise overview of various approaches to engineering ethics, the real heart of the book will be some 13 detailed case studies, delving into the history behind each one, the official outcome and the "real story#x94; behind what happened. Using a consistent format and organization for each one-giving background, historical summary, news media effects, outcome and interpretation--these case histories will be used to clearly illustrate the ethics issues at play and what should or should not have been done by the engineers, scientists and managers involved in each instance.* Covers importance and practical benefits of systematic ethical behavior in any engineering work environment.* Only book to explain implications of the Sarbanes/Oxley "Whistle-Blowing" federal legislation* 13 actual case histories, plus 10 additional "anonymous" case histories-in consistent format-will clearly demonstrate the relevance of ethics in the outcomes of each one* Offers actual investigative reports, with evidentiary material, legal proceedings, outcome and follow-up analysis* Appendix offers copies of the National Society of Professional Engineers Code of Ethics for Engineers and the Institute of Electrical and Electronic Engineers Code of Ethics.